Some Identities Involving Central Binomial Coefficients and Nielsen’s Beta Function - Jyothi, K.; Ravi, B.; Nagaraju, L.; Lakshmi, A. Venkata (Journal of Nepal Mathematical Society, 2026)
Abstract available on the full text PDF.